America's Defence of Its Partners in the Middle East. Issue 6 (2nd November 2022) - Saab, Bilal Y.
Abstract: The main factors American presidents typically consider before committing military resources to protect a partner include perceived US national interests, US domestic politics, the nature of the attack itself, the aggressor's military capabilities and the possibility of escalation. An additional factor is the ability and willingness of the partner to conduct joint and combined operations with the United States and possibly others. This is critically important in the Middle East. As Washington prioritises the Indo-Pacific and Europe, US military forces will draw down in the Middle East and be less able to intervene promptly. To maintain strong regional deterrence, security arrangements between the United States and its Arab partners should be reconfigured to ensure that they can confront regional threats, Iran's in particular, without immediate American assistance. The will require American advice and assistance in creating sustainable and effective joint forces.